PENGARUH KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP ETIKA KERJA DAN KINERJA KARYAWAN UMKM DI KABUPATEN KAMPAR - Padil Putra Firani (Pelantar Press, 2024)
MSMEs are one of the important elements in the economy, because MSMEs can survive in all economic conditions and can accommodate workers from the surrounding community. So that MSMEs play an important role in reducing the unemployment rate and improving the community's economy. Therefore, every employee in MSME must be able to provide maximum performance to the business where they work. Based on the problem of the performance of MSME employees, this study aims to analyze the influence of leadership and organizational climate on the work ethic and performance of MSME employees in Kampar Regency. This research was conducted on SMEs in Kampar Regency, especially in the Pineapple Chips business in Kualu Nenas, Tambang District, Kab. Kampar, the number of samples used was 67 employees. data collection techniques using questionnaires, and path analysis data analysis using SPSS Version 17.00. The results of the study show that: 1) Leadership influences the work ethic of employees. 2) Organizational climate affects the work ethic of employees. 3) Leadership influences employee performance. 4) Organizational climate affects employee performance. 5) Work Ethics is able to become a mediating (intervening) variable in the relationship between leadership variables and Employee Performance variables. 6) Work Ethics is able to become a mediating (intervening) variable in the relationship between organizational climate variables on Employee Performance variables. 7) Work ethic affects employee performance. The suggestions that can be given from this research are: 1) Leaders must be able to show honesty in every action, 2) Always appreciate from the office when completing work right, 3) Set an example of honest behavior by leaders, 4) Provide a good understanding to employees about the standard of work to be performed.are.